STUDY OF INVESTOR BEHAVIOR IN THE MARKET CRYPTOCURRENCY WITH AN AGENT MODEL APPROACH - Rekryanta
This study focuses on investor behavior in the cryptocurrency market using agent-based modeling and statistical-thermodynamic analysis. We utilized the NetLogo platform to develop an agent-based model that simulates how investors interact with digital assets and adapt to price fluctuations. Through this simulation, we observed the impact of investor behavior on wealth distribution within the market. Our NetLogo code encompasses decision-making, movement, and interactions with crypto assets, while thermodynamic concepts are employed to measure market uncertainty, reflecting variations in investor behavior. Our analysis identified two primary phenomena: compression and expansion of wealth distribution. Compression occurs when wealth distribution decreases after a certain period, while expansion occurs when wealth increases. The statistical analysis helps identify trends and patterns in investor behavior, as well as measure wealth concentration in the cryptocurrency market. The findings of this study provide deep insights into how investor behavior affects the cryptocurrency market, highlighting important implications for market understanding and offering guidance for investors and policymakers.